PENGARUH KENAKALAN REMAJA TERHADAP HASIL PRESTASI BELAJAR PESERTA DIDIK - Nisfah Furoidah (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
Juvenile delinquency must be addressed because it has a negative impact on students' learning achievement, because basically this stage of adolescence is where students are looking for their identity. The adolescent stage of growth is still in an unstable position, always making changing decisions. At this teenage age, many students do many new things that they want to try, without knowing whether this will have a good or bad impact on the students. So if the treatment carried out by students is negative, it will have an impact on the students themselves. Thus, this research aims to determine the percentage level between juvenile delinquency and student learning achievement results, so that it can be answered and prevented before there is further improvement. After that, students can pay more attention to all the behavior carried out by students. The research uses quantitative methods with a Likert scale in the form of a questionnaire or questionnaire. The results of research on juvenile delinquency can be addressed and prevented so that there is no further increase.